Effects of Different Balance Training Volumes on Children's Dynamic Balance - Schedler, Simon; Graf, Stella Marie; Muehlbauer, Thomas (Sports Medicine International Open, 2022)
Concerning balance training, the most effective design of several load dimensions (e. g., training frequency, volume) is unclear. Thus, we determined the effects of different balance training volumes on dynamic balance in healthy children. Three groups of 20 children (age: 11.0±0.7 years; 47% females) were randomly assigned to a balance training group using a low or a high training volume or an active control group that performed regular physical education lessons. All groups trained for 8 weeks (2 sessions/week), whereby balance training volume amounted to 4 min/session and 18–24 min/session for the low- and high-volume group, respectively. Pre- and post-training, balance performance was assessed using the Lower Quarter Y-Balance Test and the Timed-Up-and-Go Test. Fifty-five children completed the study and significant Test x Group interactions were detected for both outcome measures in favor of the two balance training groups. Additionally, improvements in the high-volume group were significantly larger for some measures (Y-balance test anterior reach distance: p<.001, d=.94; Timed-Up-and-Go time: p=.003, d=.81) compared to the low-volume group. The results indicate that balance training is effective to improve balance performance in healthy children and it seems that a 36–48 min/week compared to an 8 min/week training volume provides additional effects.
Keywords: postural control; youth; intervention; dose-response relationship